Pengelolaan Perkebunan Jeruk Nipis (Citrus aurantifolia swingle) di Desa Palem Raya, Desa Tanjung Pering, Desa Seri Bandung, Kabupaten Ogan Ilir, Provinsi Sumatera Selatan - Qanita, Zalfa; Septiani, Duwi; Salsabilla, Salsabilla; Rizkiya, Khairum; Yulinda Sari, Siska; Anggara, Fanny (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Qanita Z, Septiani D, Salsabilla S, Rizkiya K, Sari SY, Anggara F. 2022. Manajement of Lime plantation (Citrus aurantifolia swingle) in The Village of Palem Raya, Village of Tanjung Pering, Village of Seri Bandung, Ogan Ilir Regency, Sumatera Selatan Province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 302-308. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Ogan Ilir Regency is one of the lime (Citrus aurantifolia swingle) producing areas in South Sumatera, with farmers who grow lime as a household garden business for their daily life, now turning to the plantation business. However, the lack of attention from the owner in the sustainability of this plantation, so that plantation processing does not get optimal results. This survey activity aimed to determine the management of lime plantations in Palem Raya Village, Tanjung Pering Village, and Seribandung Village. The method used is direct interviews with the perpetrators and the lime garden cultivation. The results of the survey that we conducted in the 3 villages showed that lime plants experienced less than optimal productivity in terms of fruit and stem growth because they were not taken care of by their owners. Lack of care by garden owners such as not cleaning new shoots so that plants absorb nutrients optimally, applying fertilizers are not in accordance with plant needs, and pests that attack limes such as fruit flies, aphids and leafhoppers. The conclusion from this survey is the productivity of the citrus plantations in the 3 villages is less than optimal, where in the three locations the fruit produced is still experiencing a lot of damage because it is not taken care of. The advice we can give is for lime plantation farmers to do more maintenance by clearing the land, giving fertilizers at the right dose and time, and giving pesticides regularly. So that optimal product results are obtained.